2000
DOI: 10.1097/00000421-200010000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcome of Endometrial Carcinoma Patients Age 45 Years and Younger

Abstract: Recent reports have suggested that the pathologic features of young patients with endometrial cancer are less favorable than previously thought. We retrospectively reviewed the characteristics and outcome of young patients with endometrial cancer at our institution. A total of 457 surgically staged patients were divided in 2 groups: Group A (age < or =45 years, n = 41) and B (age >45, n = 416). Groups A and B had a similar distribution of tumor stage, grade, histology, lymphovascular invasion, synchronous ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 11 publications
2
51
0
3
Order By: Relevance
“…In a large scale population-based study, the 5-year disease-specific survival was 93% in women younger than 40 years (4). Younger patients with endometrial cancer often have early-stage, low-grade tumors, which may, in part, explain the higher survival of younger patients (4)(5)(6).…”
mentioning
confidence: 99%
“…In a large scale population-based study, the 5-year disease-specific survival was 93% in women younger than 40 years (4). Younger patients with endometrial cancer often have early-stage, low-grade tumors, which may, in part, explain the higher survival of younger patients (4)(5)(6).…”
mentioning
confidence: 99%
“…It has been suggested that endometrial carcinomas in young women are less aggressive and biologically different compared to those in older women [3][4][5][6][7][8][9][10] . Other investigators noted a similar incidence of extrauterine disease, unfavorable histologies and outcome in women aged 45 years or younger compared to older women [11][12][13] . There might be a difference in grade and myometrial invasion between younger and older patients, but all studies of women younger than 40 or 45 years have been limited by small numbers and permit few conclusions.…”
Section: Endometrial Cancer In Young Womenmentioning
confidence: 85%
“…Essentially, the pathologic features and outcomes of young women with endometrial cancer are reported to be similar to those of older women [9,10]. Furthermore, a recent analysis of 61,314 women in the Surveillance, Epidemiology, and End Results (SEER) cancer database from 1988 to 2003 found that younger women are more likely to be diagnosed with earlier stage disease than their older counterparts, and that their overall mean survival is significantly better [4].…”
Section: Discussionmentioning
confidence: 99%